The relationship between the plasma prolactin level and pregnancy outcome in women with recurrent spontaneous abortion. (16th November 2010) - Li, W; Laird, S; Li, TC
Abstract : Introduction: The role of prolactin in pregnancy is controversial. Earlier studies reported on the high prevalence of hyperprolactinaemia in Recurrent miscarriage (RM) and the possible deleterious role of high prolactin level in pregnancy in women with RM.1 – 3 However, recent studies have shown a beneficial role of prolactin in pregnancy through signalling decidualization and embryo implantation.4 5 Objective: >To evaluate the relationship between the prolactin concentration and pregnancy outcome in RM. Material and Methods: A consecutive series of 465 women with RM had plasma prolactin measurements in the early follicular phase. Among these women, 109 women with unexplained RM and who had subsequent pregnancies during the study period were included in the analysis. Pregnancy outcome was measured as the outcome of the first subsequent spontaneous pregnancy during the study period. Results: 1.2% (6/465) women had hyperprolactinaemia. 109 women with unexplained RM had subsequent pregnancies during the study period. The mean (±SD) age of these women was 31.9±5.2 years. The concentrations of plasma prolactin were within the normal range in all cases (mean±SD 278±146 mIU/l). 60 of the 109 women had live births and 49 had spontaneous abortions. These women were further divided into two subgroups according to the value of their prolactin concentrations. Women with prolactin concentrations above the mean had significantly higher live birth rates (66.7%) than women with prolactin concentrations below the mean (46.9%) (p<0.05). Conclusion: Low normal prolactin level is associated with an increased risk of spontaneous abortion in a subsequent pregnancy in women with RM.